The Metaverse as a Digital Missionary Site - Nam, Sung Hyuk (Ecclesial Futures, 2023)
The metaverse attracts considerable attention in politics, economy, society and culture. Unfortunately, seminaries and churches are still in their early stages of missiological research and understanding the metaverse. If we understand the metaverse as a digital mission field, research on the missiological approach is required. We should pay attention to the infinitely expanding and integrating metaverse. Overseas, there is already a history of experimental challenges and settlements from decades ago on the potential for churches in virtual spaces. While online churches are famous in Korea, there is insufficient understanding of ways to meet the younger generation of non-believers in the metaverse. Since online churches are analogue enterprises, there is a massive gap between them and the digital younger generation. Paul Hiebert’s critical contextualization is still valid in approaching the metaverse as a digital mission field. Heidi Campbell’s study of the relationship between media and religions, “religious-social shaping approach to technology” reminds Korean churches of the value of the metaverse as a new media. Both theories show Korean churches need dialogue and patience when approaching the metaverse to contact non-believers. Missiological discussions on the metaverse should promote a holistic understanding in which the two worlds closely relate rather than a dualistic understanding. The digital living space of the MZ generation that emerged with the development of new technology does not conflict with the nature of the Christian Church. Therefore, Korean churches need to understand the metaverse as a space of mission and coexistence.